PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. RAMAYANA MAKMUR SENTOSA TBK DI JAKARTA PUSAT - Putri Sokawati; Suroto (Jurnal Menara, 2025)
This study aims to analyze the influence of discipline and work motivation on employee performance at PT Ramayana Makmur Sentosa Tbk. This study is motivated by the importance of quality human resources in increasing company productivity, as well as the discovery of high performance and absenteeism rates in the company. The approach used is quantitative with a saturated sample method, involving the entire population of 63 respondents. Data collection techniques were carried out through questionnaires, while data analysis techniques used the classical assumption test, multiple linear regression analysis, t-test and F-test, and coefficient of determination. The results of the study indicate that discipline and work motivation have a positive and significant effect on employee performance. The results of this study are Discipline has a significant effect on employee performance with a determination coefficient value of 45.1% and the hypothesis test obtained t count> t table or (7.076> 1.670). Motivation has a significant effect on employee performance with a determination coefficient value of 50.9% and the hypothesis test obtained t count> t table or (7.959> 1.670). Discipline and motivation simultaneously have a significant effect on employee performance with the regression equation Y = 26.224 + 0.0099X1 + 0.257X2. The determination coefficient value is 55.3% while the remaining 44.7% is influenced by other factors. Hypothesis testing obtained the value of F count > F table or (37.063 > 2.091).